Improving automotive accessory development: a warranty-based analysis of material defects and process enhancement - Ismail, Mohd Fauzi; Abdul Hamid, Nor Hissham; Mahamad Basri, Mahamad Hisyam; Adull Manan, Nor Fazli (Smart Manufacturing Research Institute (SMRI), 2025)
Automotive accessories play a crucial role in enhancing vehicle safety, aesthetics, and functionality; however, they account for a significant portion of recurring warranty claims at MNC Automotive. In 2022, analysis of warranty claims data revealed that 30% of total claims were attributed to a single accessory type, indicating systemic weaknesses in design validation, supplier performance, and quality assurance. To address these challenges, this study proposed an improved accessory part development process that emphasizes early supplier collaboration, comprehensive design validation, statistical validation methods (such as SPC, Regression Analysis and Confidence Intervals), and standardized manufacturing practices. The study integrated SPC (Control Charts) and regression analysis to validate defect trends and link supplier performance with defect rates, offering quantitative validation beyond qualitative tools like Pareto charts and Ishikawa diagrams. Confidence intervals were calculated to estimate defect reduction, providing a statistical basis for the improvement strategies. Furthermore, the study included a cost-saving analysis, indicating potential RM 1.5 million savings, which was estimated through a cost-benefit analysis that simulates the ROI from improved processes. Incorporating comparative benchmarking with historical data allows us to track the severity and progress of improvements in defect rates and warranty claims. Additionally, the study integrated a more detailed evaluation of supplier performance, where supplier audits and performance ratings were used to identify critical areas for improvement in quality control. The proposed part development process aligns with APQP, PPAP, and IATF 16949 frameworks, ensuring that the model conforms to globally recognized quality management standards. Key elements of these frameworks, such as early engagement, traceability, and continuous improvement cycles, were incorporated to address recurring quality issues, thereby improving product reliability, reducing defects, and strengthening supplier relationships. This study contributes to the broader field of automotive engineering by offering a data-driven approach to improving the manufacturing and supply chain processes, with implications for reducing long-term costs, enhancing product quality, and improving customer satisfaction. By addressing key weaknesses in supplier collaboration, design validation, and quality assurance, the proposed improvements are expected to lead to significant reductions in warranty claims, ultimately benefiting both manufacturers and consumers.